Islamic transcendental wellbeing model for Malaysian Muslim women: implication on counseling - Hassan, Siti Aishah (Canadian Center of Science and Education, 2015)
A great majority of the middle-aged women experience some degenerative physical symptoms, specifically pelvic prolapse which affected their quality of life. Accordingly, they experience marital distress and may lead to divorces and depression. For younger women, among college students, cybersex addiction may likely affect their academic performances. Female are double as compared to male in sexual addiction. Recent findings indicate that, spiritual wellbeing is the most satisfied domain among women in Malaysia. Yet, it does not correlate well with other domains, especially in economic. For single mothers, socio-economic status is indeed in crisis. Hence, there is a need to capitalize women’s spirituality as inner resources for Muslim women’s wellbeing. Therefore, we conceptualize a holistic model for Muslim Malaysian women wellbeing that integrates physical-sexual, socio-economical, and psycho-spiritual domains. Theoretically, this model helps to delineate Islamic transcendental theory that explains spiritual wellbeing permeates overall wellbeing. Finally, implications on counselling process are suggested.